PENDIDIKAN TOLERANSI DALAM PEMBELAJARAN BAHASA INDONESIA BERBASIS METODE THINK PAIR SHARE DI STIKOM BALI - Ni Nyoman Ayu Suciartini (LP3M Universitas PGRI Mahadewa Indonesia, 2018)
Schools, teachers, colleges, and education in general, are integral parts of each other. Education should not turn a blind eye to the intolerant view that now adorns social media, screen, even print media. Educational institutions should be able to reaffirm the values ​​of tolerance to keep education quality and not hindered issues of racism. The face of learning in education, especially in college must maintain the diversity that becomes the foundation of pluralism full of life. Education tolerance should be re-strived stronger, more attached. Teachers must be responsive and not to be eclectic and neither do they tackle the issue of this epidemic. The nature of racism is not a human nature. For that the spread is very likely destroyed. The practice of intolerance in the education line has been addressed wisely. One of them is by reviving the spirit of tolerance education in harmony with the education of multiculturalism. If these intolerant and racism behaviors deepen into the world of education, the graduates produced will not be able to form a characterized person as mandated in the Pancasila and the Constitution. So what should be hastened to counter intolerance at schools, universities and educational institutions so that the quality of education and resources will not be disturbed and remain qualified? Education can’t be separated from social turmoil in society. This will have a direct impact, especially on the character of the students. For this reason, the planting of tolerance values ​​in important college learning is revived to prevent intolerant practices in education, especially in universities.